Myo-Inositol Restores Tilapia’s Ability Against Infection by Aeromonas sobria in Higher Water Temperature - Yang, Man-jun; Jiang, Ming; Peng, Xuan-xian; Li, Hui (Frontiers in Immunology, 2021)
Bacterial infection presents severe challenge to tilapia farming, which is largely influenced by water temperature. However, how water temperature determines tilapias’ survival to infection is not well understood. Here, we address this issue from the perspective of metabolic state. Tilapias were more susceptible to Aeromonas sobria infection at 33 0C than at 18 0C, which is associated with differential metabolism of the fish. Compared to the metabolome of tilapia at 18 0C, the metabolome at 33 0C was characterized with increased tricarboxylic acid cycle and reduced level of myo-inositol that represents the most impactful pathway and crucial biomarker, respectively. These alterations were companied with the elevated transcriptional level of ten innate immune genes with infection time, where il-1b, il-6, il-8, il-10 exhibited higher expression at 33 0C than at 18 0C and was attenuated by exogenous myo-inositol in both groups. Interestingly, exogenous myo-inositol inactivated the elevated TCA cycle via inhibiting the enzymatic activity of succinate dehydrogenase and malate dehydrogenase. Thus, tilapias showed higher survival ability at 33 0C. Our study reveals a previously unknown relationship among water temperature, metabolic state and innate immunity and establishes a novel approach to eliminate bacterial pathogens in tilapia at higher water temperature.